Cortical Responses to Thermal Pain Depend on Stimulus Size: A Functional MRI Study - Apkarian, A. Vania; Gelnar, Patricia A; Krauss, Beth R; Szeverenyi, Nikolaus M (Journal of neurophysiology, 2000)
1 Department of Neurosurgery and 2 Department of Radiology, State University of New York Upstate Medical University, Syracuse, New York 13210 Apkarian, A. Vania, Patricia A. Gelnar, Beth R. Krauss, and Nikolaus M. Szeverenyi. Cortical Responses to Thermal Pain Depend on Stimulus Size: A Functional MRI Study. J. Neurophysiol. 83: 3113-3122, 2000. Cortical activity patterns to thermal painful stimuli of two different sizes were examined in normal volunteers using functional magnetic resonance imaging (fMRI). Seven right-handed subjects were studied when the painful stimulus applied to the right hand fingers covered either 1,074-mm 2 -area large stimulator or 21-mm 2 -area small stimulator. Stimulus temperatures were adjusted to give rise to equivalent moderately painful ratings. fMRI signal increases and decreases were determined for the contralateral parietal and motor areas. When the overall activity in these regions was compared across subjects, increased fMRI activity was observed over more brain volume with the larger stimulator, whereas decreased fMRI activity was seen in more brain volume for the smaller stimulator. The individual subject and group-averaged activity patterns indicated regional specific differences in increased and decreased fMRI activity. The small stimulator resulted in decreased fMRI responses throughout the upper body representation in both primary somatosensory and motor cortices. In contrast, no decreased fMRI signals were seen in the secondary somatosensory cortex and in the insula. In another seven volunteers, the effects of the size of the thermal painful stimulus on vibrotactile thresholds were examined psychophysically. Painful stimuli were delivered to the fingers and vibrotactile thresholds were measured on the arm just distal to the elbow. Consistent with the fMRI results in the primary somatosensory cortex, painful thermal stimuli using the small stimulator increased vibrotactile thresholds on the forearm, whereas similarly painful stimuli using the large stimulator had no effect on forearm vibrotactile thresholds. These results are discussed in relation to the cortical dynamics for pain perception and in relation to the center-surround organization of cortical neurons.